2019
DOI: 10.3390/cancers11122040
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Silica-Coated Iron Oxide Nanochains as Photothermal Agents, Disrupting the Extracellular Matrix, and Eradicating Cancer Cells

Abstract: Cancerous cells and the tumor microenvironment are among key elements involved in cancer development, progression, and resistance to treatment. In order to tackle the cells and the extracellular matrix, we herein propose the use of a class of silica-coated iron oxide nanochains, which have superior magnetic responsiveness and can act as efficient photothermal agents. When internalized by different cancer cell lines and normal (non-cancerous) cells, the nanochains are not toxic, as assessed on 2D and 3D cell cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Increasing information has been presented on existing links between matrix stiffness and cancer prognosis [86]. Indeed, the aberrant production of ECM leading to tumour stiffening has been Similarly, another study described that hyperthermia performed on tissue-engineered human dermal substitutes loaded with magnetic iron oxide nanochains provoked cell death and collagen melting [95].…”
Section: Hyperthermia Based On Nanoparticles Is An Efficient Way To Rmentioning
confidence: 99%
“…Increasing information has been presented on existing links between matrix stiffness and cancer prognosis [86]. Indeed, the aberrant production of ECM leading to tumour stiffening has been Similarly, another study described that hyperthermia performed on tissue-engineered human dermal substitutes loaded with magnetic iron oxide nanochains provoked cell death and collagen melting [95].…”
Section: Hyperthermia Based On Nanoparticles Is An Efficient Way To Rmentioning
confidence: 99%
“…In particular, their morphological anisotropy opens new possibilities to exploit magneto-mechanical effects in the treatment of diverse diseases, because nanochains can follow the rotational movement of rotating magnetic field at low frequencies (up to hundreds of Hz), contrarily to individual spherical nanoparticles [ 115 , 116 ]. Such a movement of rigid nanochains can transduce the magnetic force into mechanical torque exerting on a nearby targeted tissue [ 36 ]. Alternatively, their rotational movement can accelerate drug release from the nanochain surface on demand, and this represents a radically new means of controlled drug release [ 94 ].…”
Section: Biomedical Applications Of Magnetic Nanochainsmentioning
confidence: 99%
“…Recently, the photothermal effectiveness of IONs has been proved to depend on particle size: The effectiveness shows a good correlation with particle volume [25]. Several works using aggregated or individual IONs as PA in the first biological window have been described [26][27][28][29][30][31][32]. In this way, Yuan et al demonstrated that IONs coated with polyethylene glycol (PEG) presented anti-cancer activity [33].…”
Section: Introductionmentioning
confidence: 99%